2012
DOI: 10.1007/s11999-011-2222-2
|View full text |Cite|
|
Sign up to set email alerts
|

Do Patient-specific Guides Improve Coronal Alignment in Total Knee Arthroplasty?

Abstract: Background Coronal alignment may impact clinical outcome and survivorship in TKA. Patient-specific instrumentation has been developed to restore mechanical or kinematic axis and potentially reduce component malpositioning. Although it is clear these instruments add cost, it is unclear whether they improve alignment. Questions/purposes We determined whether the mean coronal alignment after TKA performed with conventional versus patient-specific instrumentation better restored the mechanical and kinematic axes a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
175
2
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 211 publications
(182 citation statements)
references
References 29 publications
4
175
2
1
Order By: Relevance
“…They are in line with other studies of PSI which reported improved alignment [16,30,38]. Although it should be noted that other studies have failed to show a clear advantage for PSI technology [24,32], and that one study with the technology employed in the current analysis observed only a fair rate of accuracy, with higher risk of error >3°in the sagittal plane [11], there does appear to be an overall trend for the superiority of these new technologies over earlier instrumentation methods.…”
Section: Discussionsupporting
confidence: 89%
“…They are in line with other studies of PSI which reported improved alignment [16,30,38]. Although it should be noted that other studies have failed to show a clear advantage for PSI technology [24,32], and that one study with the technology employed in the current analysis observed only a fair rate of accuracy, with higher risk of error >3°in the sagittal plane [11], there does appear to be an overall trend for the superiority of these new technologies over earlier instrumentation methods.…”
Section: Discussionsupporting
confidence: 89%
“…Our study was designed to verify the utility of CT-based Signature™ PSI for precise implant positioning. In general, results of studies on PSI are equivocal [8,15,[25][26][27][28]. We believe that results obtained with one particular PSI system are not automatically applicable to other systems and should not be generalised [14,23].…”
Section: Discussionmentioning
confidence: 93%
“…At the moment, several companies offer various PSI systems for TKA. Custom-made guides may be designed to align components along the mechanical axis or in relation to a natural transcylindrical axis [8,29,30 ]. There are pinning systems that determine accurate pin placement for the standard resection instrumentation, and cutting guides with immediately integrated resection blocks [3,17,29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All patients received postoperative coronal scout CT scans of the HKA with the extremities rotated into a neutral position to standardize the measurements using a previously described method [26]. The HKA axis, which is the angle formed between the mechanical axis of the femur (the line connecting the center of the femoral head with the center of the knee) and the mechanical axis of the tibia (the line connecting the center of the ankle mortise to the center of the knee), was measured in all patients with a targeted postoperative HKA alignment of 0°± 3°.…”
Section: Methodsmentioning
confidence: 99%